SOIL PROPERTIES BELOW EXOTIC TREE PLANTATIONS AT THE SAITHONG SILVICULTURAL RESEARCH STATION IN PRACHUAP KHIRI KHAN PROVINCE, THAILAND - Kanokwan Urairak; Roongreang Poolsiri; San Kaitpraneet (SEAMEO BIOTROP, 2020)
Often, exotic trees grow very fast in their new environments and sometimes even faster than the indigenous ones. These exotics seem to be tougher and able to live through harsher conditions. They may be drought-resistant and can survive long periods with little to no rainfall. These trees are fast-growing and resistant to pests and diseases that tend to damage locally growing trees. Moreover, these trees can help improve soil physical and chemical properties. Hence, the objective of this study was to compare the physical and chemical properties of soils under different tree plantations, namely Eucalyptus urophylla, Acacia crassicarpa, and Acacia auriculiformis at the Saithong Silvicultural Research Station. Three composite soil samples were collected from depths of 0–10, 10–30, and 30–50 cm in the three stands aged 27 years and planted at a spacing of 2 × 2 m. The soil type in these stands was sandy loam. Soil moisture percentage (12.85%) was significantly the highest in the E. urophylla plantation. Phosphorus (18.2 mg/kg), magnesium (6.98 cmolc/kg DW), and potassium (6.98 cmolc/kg DW) contents were also the greatest in the E. urophylla plantation. Organic matter content was the highest in the A. crassicarpa plantation (7.59%), while nitrogen (0.04%) and calcium (36.17 cmolc/kg DW) contents were the highest in the A. auriculiformis plantation. Significant differences were also observed in soil bulk density and porosity attributable to structure, tillage, cropping practices, soil depth, and compaction. Characterization of the soil pore system is equally important in understanding soil physical properties and parent material composition, which has a direct impact on soil chemistry and fertility. Parent material rich in soluble ions (calcium, magnesium, potassium, and sodium) is desirable, as these elements are easily dissolved in water and readily available for plants. For soils with poor nutrient content found in warm and humid tropical climates with low water supply, E. urophylla, A. crassicarpa, and A. auriculiformis have the potential to enhance aboveground stand production. Undoubtedly, when planted, they can help restore soil nutrients faster and therefore can be used in forest plantations or agroforestry farms.